Virtual Tourism Android-Based Application - Saurabh Dubal,; Vishal Raut,; Dinesh Choughule,; Pravin Shinde,; S.A. Hajare, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The Virtual Tourism- Android-based Application revolutionizes the tourism indus try by offering users a unique opportunity to explore global destinations from the comfort of their homes. Leveraging cutting-edge technologies such as 360-degree panoramic views, augmented reality (AR), and interactive multimedia, the app cre ates an immersive and engaging travel experience that brings famous landmarks, historical sites, and natural wonders to life. This application is especially valuable for individuals who face physical, financial, or time-related constraints, allowing them to virtually visit locations they may oth erwise be unable to access. It also serves as an educational tool, enabling students and culture enthusiasts to learn about the world in a highly interactive and accessible manner. The real-time tour guides and interactive maps add a dynamic layer to the virtual exploration, enhancing user engagement. In addition to these features, the app integrates social media sharing, user reviews, and offline access, fostering a community-driven platform where users can share their experiences, rate destinations, and download content for use without internet connectivity. This comprehensive combination of innovative features positions the Virtual Tourism app as a game-changer in the future of travel and education.
Keywords: Mobile Technology; Destination Exploration; Tourism innovation; Digital travel; Smartphone Application